COMPARATIVE-TYPOLOGICAL STUDY OF PROVERBES WITH THE SOMATIC COMPONENT “HEAD/BOSH/ ГОЛОВА” IN DIFFERENT SYSTEMIC LANGUAGES (Scientific journal of the Fergana State University, 2023)
This article deals with the issue of provebemes of monotaxemic and polytaxemic structure with the somatic component head in English, Uzbek and Russian, where the emphasis is made on identifying their structural-semantic types, revealing their isomorphic and allomorphic features and the factors preconditioning the latter.